Þingeyrar Abbey in Northern Iceland: A Benedictine Powerhouse of Cultural Heritage - Gottskálk Jensson (Religions, 2021)
Þingeyrar Abbey was founded in 1133 and dissolved in the wake of the Lutheran Reformation (1550), to virtually disappear with time from the face of the earth. Although highly promising archeological excavations are under way, our material points of access to this important monastic foundation are still only a handful of medieval artifacts. However, throughout its medieval existence Þingeyrar Abbey was an inordinately large producer of Latin and Icelandic literature. We have the names of monastic authors, poets, translators, compilators, and scribes, who engaged creatively with such diverse subjects as Christian hagiography, contemporary history, and Norse mythology, skillfully amalgamating all of this into a coherent, imaginative whole. Thus, Þingeyrar Abbey has a prominent place in the creation and preservation of the Icelandic Eddas and Sagas that have shaped the Northern European cultural memory. Despite the dissolution of monastic libraries and wholesale destruction of Icelandic-Latin manuscripts through a mixture of Protestant zealotry and parchment reuse, philologists have been able to trace a number of surviving codices and fragments back to Þingeyrar Abbey. Ultimately, however, our primary points of access to the fascinating world of this remote Benedictine community remain immaterial, a vast corpus of medieval texts edited on the basis of manuscript copies at unknown degrees of separation from the lost originals.